2014
DOI: 10.7863/ultra.33.5.793
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Radiation Force Impulse Elastography of the Kidneys

Abstract: Objectives The aim of this study was to identify the main influencing factor of the shear wave velocity (SWV) of the kidneys measured by acoustic radiation force impulse elastography. Methods The SWV was measured in the kidneys of 14 healthy volunteers and 319 patients with chronic kidney disease. The estimated glomerular filtration rate was calculated by the serum creatinine concentration and age. As an indicator of arteriosclerosis of large vessels, the brachial‐ankle pulse wave velocity was measured in 183 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(43 citation statements)
references
References 25 publications
2
40
0
1
Order By: Relevance
“…This is an interesting finding, different from the results of liver elastography and in line with the recently published data by Guo et al [39] and also by our group [42] which evaluated the kidney shear wave speed by ARFI elastography in healthy volunteers and patients with different impairment of renal function. These data suggest that factors other than interstitial fibrosis have an important role in kidney shear wave speed measurements, one of them being renal blood flow [26].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This is an interesting finding, different from the results of liver elastography and in line with the recently published data by Guo et al [39] and also by our group [42] which evaluated the kidney shear wave speed by ARFI elastography in healthy volunteers and patients with different impairment of renal function. These data suggest that factors other than interstitial fibrosis have an important role in kidney shear wave speed measurements, one of them being renal blood flow [26].…”
Section: Discussionmentioning
confidence: 84%
“…[22]–[24] It is possible that kidney shear wave speed measured using ARFI elastography is influenced by renal blood flow as well. [25], [26].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholar speculated the differences of histological changes and mechanical property between kidney and liver result in this inconsistency [14] . Asano et al [26] reported the degree of interstitial fibrosis in the kidneys of CKD is not as marked as that in chronic liver disease and suspected interstitial fibrosis is not the main affecting factor of ARFI elastography in the kidneys tissue elasticity.…”
Section: Discussionmentioning
confidence: 98%
“…One explanation for these inconsistent results may be the relatively small number of patients in Wang et al's study. Another hypothesis was that the structural heterogeneity of renal parenchyma and the diminished renal blood flow impacted on the SWV values in patients with CKD [26] .…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this difference remains unclear. Asano et al hypothesized that the decreased renal blood flow in patients with CKD reduces kidney stiffness, resulting in decreased shear wave velocities 107.…”
Section: Clinical Applications Of Ultrasound Elastographymentioning
confidence: 99%